International exploration economics, risk, and contract analysis - Johnston, Daniel (PennWell, 2003)
Annotation Deals with international exploration economics and petroleum fiscal system analysis and design and contains the most up-to-date information and discussions in the industry on the subject.
Keywords: Petroleum industry and trade -- Finance.; Petroleum industry and trade -- Management.; International business enterprises -- Finance.; elektronické knihy; electronic books